Interactive collaborative robotics : 5th International Conference, ICR 2020, St Petersburg, Russia, October 7-9, 2020, Proceedings /: 5th International Conference, ICR 2020, St Petersburg, Russia, October 7-9, 2020, Proceedings. ([2020]) - Unknown
No abstract available